Nonlinear Control of an Open-Loop Open-Winding Motor System with Modulated Converters - Oleschuk V.I. (Problems of the Regional Energetics, 2017)
Purpose of this work - to provide wider control opportunities for multiphase open-end winding motor drive by modification of basic scheme of space-vector pulse-width modulation (PWM). It has been shown, that the proposed development of basic PWM scheme insures available solutions for realization of specific control dependences and modes of operation of adjustable speed ac drives with different types and kinds of loads. Suitable algorithms of PWM of converters of multiphase drive have been analyzed and compared. Extensive simulation studies have been executed for evaluation of performance and effectiveness of the proposed control strategy. Assessment of harmonic composition of the phase voltages of drive system with modified scheme of space-vector modulation has been done. Results of the executed simulations proved the fact, that the developed techniques of space-vector pulse-width modulation allow providing quarter-wave or half-wave symmetry of waveforms of the output voltage of six-phase adjustable speed drive systems during the analyzed non-standard modes and regimes of its operation.